TYPOLOGICAL COMMONALITY AND LOCAL SPECIFICITY OF CONTEMPORARY ART DEVELOPMENT IN CENTRAL ASIA - Rakhimovna, Akhmedova Nigora; Bakhtiyarovna, Umarova Dildora (The journal of contemporary issues in business and government, 2021)
In the epoch of globalization, problems of national cultures development, the preservation of their originality and interaction with other nations stay actual in the humanities. The research of the typological community and local specifics of art in the independent states of Central Asia makes it possible to determine the main development trends. They are studied in the context of national self-awareness raise, the formation of new priorities in the art of the region, the actualization of ethnocultural identity’s issues and the restoration of links with traditional culture. An appeal to the origins of civilizational identity is shown on the example of the region's contemporary art.